RANCANG BANGUN SISTEM KONTROL DAN SISTEM PROTEKSI MOTOR LISRIK TERHADAP PANAS (OVER HEATING) SERTA PERINGATAN DINI TERHADAP GANGGUAN TEGANGAN DAN ARUS BERBASIS ATMEGA 328 - Moh Sholeh; Affan Bachri; Arief Budi Laksono (Universitas Islam Lamongan, 2018)
Electric motor is the type of motor that is most often used in everyday life. This is because the electric motor has several advantages that are not owned by a DC motor, which is simple construction and the price is quite cheap. However, if the motor is used continuously can experience heat or over heat, which can cause the motor to be damaged or burned. To overcome these problems required a system that can secure the motor from the heat that caused by the motor is often in use. This tool uses LM35 temperature sensor and is able to keep the motor always at its optimum temperature. In this system is also installed voltage sensors and current sensors to read the value of voltage and the current required by the motor. The value of temperature, current and voltage are displayed on LCD 2x16. In serial communication, initialization of baudrate on micro controller Atmega 328 is adjusted with baudrate computer, that is equal to 9600 bps. The system will provide a buzzer sound alert when the temperature reading is at 80.51ºC. Sensor LM35 function to read the temperature on the motor, when the motor is given a voltage source 220 V. At the time of the motor with a temperature of 31.74ºC up to 75.20 ºC motor in a safe state, but at temperatures above 80.51 º C motor in the state of overheating then there is a response from the micro controller to activate the relay so that the relay will break the voltage that flows on the motor and cause the motor to stop automatically, and buzzer gives a warning that the motor overheating. If this warning is allowed it can cause the motor to burn and will cause much greater repair costs.